APLIKASI LINKEDIN DALAM PERSPEKTIF KONSTRUKSI SOSIAL TEKNOLOGI - Destiyanti, Delfi; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 3 No 1 (2023): JISSOROT, 2023)
The focus of this research includes the impact of using LinkedIn on users as well as the development of this social media. The purpose of the study is to explain and analyze the social construction of technology on LinkedIn. The method used is qualitative with a descriptive-explanatory approach. The social construction of technology theory proposed by Pinch and Bijker was used to analyze this research. This research reveals that LinkedIn users utilize the platform to search for job vacancies, enhance knowledge and skills applicable in the workplace, expand their professional networks, build their personal image, and increase visibility through personal branding. Furthermore, the study shows that the use of LinkedIn has a positive impact on the career development of its users. This research also emphasizes the importance of digital presence on LinkedIn, which can be linked to the numerous benefits that LinkedIn provides, particularly in today's highly competitive job market.